You have the correct answer. It is choice B) -1/4
=======================================================
Explanation:
This is because we're adding -1/4 to each term to get the next one. In other words, we're subtracting 1/4 from each term to get the next one.
- term2 = term1+(d) = 1/2 + (-1/4) = 1/2 - 1/4 = 2/4 - 1/4 = 1/4
- term3 = term2+(d) = 1/4 + (-1/4) = 1/4 - 1/4 = 0
- term4 = term3+(d) = 0 + (-1/4) = 0 - 1/4 = -1/4
- term5 = term4+(d) = -1/4 + (-1/4) = -2/4 = -1/2
and so on.
----------
To find the common difference, all we have to do is subtract any term from its previous one.
For example:
d = (term2) - (term1)
d = (1/4) - (1/2)
d = (1/4) - (2/4)
d = (1-2)/4
d = -1/4
The order of subtraction matters, so we cannot say d = term1-term2.
Answer:nah
Step-by-step explanation:
Answer:
looks like D...............
Hello,
h(x)'=(f(x)*g(x))'=f'(x)*g(x)+f(x)*g'(x)
h(1)=f'(1)*g(1)+(f(1)*g'(1)=-4*3+4*(-3)=-24
Answer B
Mult. the 2nd eqn by 6 and then add this "new" equation to the 1st given eqn:
-6x + y = -2
6x -18y = 54
--------------------
-17y = 52, or y = -52/17. Subst. this value of y into either equation to find the value of x.